MiR-2 family targets awd and fng to regulate wing morphogenesis in Bombyx mori - Ling, Lin (RNA Biol, 2015)
MicroRNAs (miRNAs) are post-transcriptional regulators that target specific mRNAs for repression and thus play key roles in many biological processes, including insect wing morphogenesis. miR-2 is an invertebrate-specific miRNA family that has been predicted in the fruit fly, Drosophila melanogaster, to be involved in regulating the Notch signaling pathway. We show here that miR-2 plays a critical role in wing morphogenesis in the silkworm, Bombyx mori, a lepidopteran model insect. Transgenic over-expression of a miR-2 cluster using a Gal4/UAS system results in deformed adult wings, supporting the conclusion that miR-2 regulates functions essential for normal wing morphogenesis. Two genes, abnormal wing disc (awd) and fringe (fng), which are positive regulators in Notch signaling, are identified as miR-2 targets and validated by a dual-luciferase reporter assay. The relative abundance of both awd and fng expression products was reduced significantly in transgenic animals, implicating them in the abnormal wing phenotype. Furthermore, somatic mutagenesis analysis of awd and fng using the CRISPR/Cas9 system and knock-out mutants also resulted in deformed wings similar to those observed in the miR-2 overexpression transgenic animals. The critical role of miR-2 in Bombyx wing morphogenesis may provide a potential target in future lepidopteran pest control.